KEKERASAN SIMBOLIK PADA PROGRAM ACARA FESBUKERS RAMADAN 2017 DALAM SEGMEN RUMAH MIRING (RUMING) EDISI BUKA PUASA - FIRDA YAHYA; MUHAMMAD YUSUF AR (Jurnal Dakwah Tabligh, 2018)
Symbolic violence is not physical or psychological violence. If these two forms of violence can be easily recognized, symbolic violence is very difficult to recognize. Symbolic violence can occur at any time and without realizing it. The purpose of this study is to find out the symbolic violence that is present in the program "Pesbukers Ramadan 2017" in the sloping (Ruming) house segment of the break fasting edition. This study uses a mix of methods or a mixture of qualitative and quantitative methods. There are 30 episodes studied, each lasting approximately 10 minutes. The results of this study indicate, there are 298 times the occurrence of symbolic violence in the Pesbukers Ramadan program in the sloping home segment, as well as the many meanings of semiotics of violence that arise in the program both euphemism, swear, sexual, and attributes.